Answer:
(c)
![(2v_0(v_1+v_2))/(v_1+v_2+2v_0)](https://img.qammunity.org/2020/formulas/physics/middle-school/qz04f3dgr5f2yvnkqztzt7j39vdigq9ghd.png)
Step-by-step explanation:
Average speed is calculated as (total distance)/(total time). We have three segments in the journey, indexed by 0, 1, and 2:
![v = (s)/(t)=(v_0t_0+v_1t_1+v_2t_2)/(t_0+t_1+t_2)\\t_1=t_2\implies\\v=(v_0t_0+v_1t_1+v_2t_1)/(t_0+t_1+t_1)=(v_0t_0+v_1t_1+v_2t_1)/((v_0t_0)/(v_0)+(v_1t_1)/(v_1)+(v_2t_1)/(v_2))](https://img.qammunity.org/2020/formulas/physics/middle-school/viaui121op2irfn2b5fpgg1oh8my9bomq3.png)
We also know that the distance of the first segment is the same as one of segment 2 and 3 together:
![v_0t_0=v_1t_1+v_2t_1\\v_0(t_0)/(t_1)=v_1+v_2](https://img.qammunity.org/2020/formulas/physics/middle-school/6bkp5yj3giv3o81osmf8nuex1uk1e1nlqs.png)
Going back to the average speed expression, divide by t_1:
![(v_0t_0+v_1t_1+v_2t_1)/((v_0t_0)/(v_0)+(v_1t_1)/(v_1)+(v_2t_1)/(v_2))=((v_0t_0)/(t_1)+v_1+v_2)/((v_0t_0)/(v_0t_1)+2)](https://img.qammunity.org/2020/formulas/physics/middle-school/lusp4d1sax738spvv7x6dxbslasxtygguf.png)
and combine the two equations:
![((v_0t_0)/(t_1)+v_1+v_2)/((v_0t_0)/(v_0t_1)+2)=(2(v_1+v_2))/((v_1+v_2)/(v_0)+2) = (2v_0(v_1+v_2))/(v_1+v_2+2v_0)](https://img.qammunity.org/2020/formulas/physics/middle-school/blbetpykhaihtdbx6ylyhib6vrsvjbo4hh.png)
The last form matches your choice (c).